Intention to Use PayLater among Young Muslim Consumers: The Role of Islamic Religious Commitment - Sulhaini Sulhaini; Baiq Handayani Rinuastuti; Siti Nurmayanti (Journal of Consumer Sciences)
Background: Compared to other consumer groups, young Indonesian consumers have a stronger desire for debt and overconsumption